Evaluation of Reference Dilution Test Methods for Antimicrobial Susceptibility Testing of Pseudomonas aeruginosa Strains Isolated from Patients with Cystic Fibrosis - Saiman, Lisa (American Society for Microbiology, 1999)
The development of multidrug-resistant Pseudomonas aeruginosa in patients with cystic fibrosis (CF) is most likely a consequence of increasing life expectancy and more prolonged exposure to antibiotics. The optimal method for antibiotic susceptibility testing of CF strains, particularly mucoid P. aeruginosa strains, is unknown. Antimicrobial susceptibilities of 48 CF strains (25 mucoid) and 50 non-CF strains to 12 anti-Pseudomonas agents were tested by both agar dilution and commercially custom-prepared broth microdilution plates (PML Microbiologicals, Portland, Oreg.) in three laboratories simultaneously to determine if broth microdilution could substitute for agar dilution as the reference method in subsequent studies. Comparison of MICs generated by agar dilution and broth microdilution demonstrated correlation coefficients (r) exceeding 0.85 for all agents tested; correlation was excellent for aminoglycosides (r ≥ 0.92) and very good for β-lactam agents including agents paired with a β-lactamase inhibitor (r ≥ 0.87) and for ciprofloxacin (r = 0.86). Correlation was not improved by 48-h readings, but correlation between 24- and 48-h readings ranged between 0.91 and 0.98 for both methods. Interlaboratory variations were minimal, as the percentage of acceptable variations was 94% for both methods, and serious discords were infrequent (<2% of comparisons). However, CF strains were more likely to have serious discords than were non-CF strains (P < 0.0001), although mucoid strains were not more likely to have serious discords than were nonmucoid strains. In this study, MICs determined by custom-prepared broth microdilution compared favorably with MICs determined by agar dilution. Thus, this broth microdilution assay can serve as a reference method and facilitate future studies to determine the optimal method for antibiotic susceptibility testing of CF strains.